Education as a sociological foundation: From individual formation to global citizenship - Gayatri Sunkad; Majid Wajdi; Norhayati Mohd Yusof; QingHao Wu (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This paper examines the intrinsic relationship between education and society, emphasizing education's role as a foundational force in individual development and societal organization. The study aims to conceptualize education beyond the narrow framework of literacy, focusing instead on its broader sociological implications—particularly its capacity to cultivate moral values, civic responsibility, and social cohesion. Employing a qualitative, document-based research methodology, the study draws upon classical and contemporary philosophical perspectives, including those of Mahatma Gandhi and Aristotle, to elucidate the dynamic interplay between the individual, the community, and educational structures. The analysis highlights that education begins within the family unit, where fundamental human values such as empathy, compassion, and cooperation are first transmitted. As formal education expands this foundation, individuals become better equipped to engage constructively with increasingly complex social institutions—from the family and village to the state and global society. The study also outlines how these interconnected social layers evolve, underscoring the necessity of education in sustaining and advancing collective human life. In conclusion, education emerges not merely as a process of intellectual acquisition but as a transformative social force that shapes ethical individuals and cohesive communities. To ensure long-term societal well-being, it is imperative that educational systems integrate cognitive, emotional, and ethical dimensions, thereby enabling individuals to function as conscientious members of a global society.